Nozima BORROWINGS OF ENGLISH WORDS IN YOUTH SOCIOLECT: BORROWINGS OF ENGLISH WORDS IN YOUTH SOCIOLECT - Akramova, Nozima (Журнал иностранных языков и лингвистики, 2022)
The article under discussion depicts borrowings of English words in the speech of young people in Uzbekistan and the ways of their formation. Besides, a detailed classification of English loanwords are presented. The author of the article considers that English words are more readily borrowed mostly by young people. New words in the youth speech can be formed according to existing models in the language, borrowed from other languages, appear as a result of the development of new meanings in already known words.